Effects of biochar and wood ash amendments in the soil-water-plant environment of two temperate forest plantations - Moragues-Saitua, Lur; Arias-González, Ander; Blanco, Fernando; Benito-Carnero, Garazi; Gartzia-Bengoetxea, Nahia (Frontiers in Forests and Global Change, 2023)
Forest biomass is considered an alternative to fossil fuels in energy production, as part of global strategies for climate change mitigation. Application of by-products such as wood ash (WA) and biochar (BC) to soil could replace the nutrients removed by tree harvesting and could also increase soil carbon stocks. However, the extent to which these amendments can provide benefits depends on how the by-products interact with the soil-water-plant system. We studied the short-term responses of WA and BC application in two different mineral soil-water-plant systems in temperate forests: A. Typic Udorthent (TU) with mature Pinus radiata; B. Typic Dystrudept (TD) with young Quercus pyrenaica, to test the following hypotheses: (1) the application of WA and BC will increase nutrient uptake by plants, but (2) these products could induce toxicity in the soil-water-plant system, and (3) in case of no toxicity, plant biomass growth in these temperate forest soils will increase due to increased plant nutrient uptake. Biochar was applied at rates of 3.5, 10, and 20 Mg ha–1 and WA at rates of 1.5, 4.5, and 9 Mg ha–1 (calcium equivalent). A nitrogen enriched treatment was applied with the intermediate doses. Ecotoxicity testing indicated that WA and BC were not toxic, although Ni uptake increased in biomass of the TU after BC + N application. BC increased SOC stocks of both sites, depending on treatment. In TD BC increased K uptake by plants, but did not increase biomass. In summary, this study shows that the application of BC and WA had different effects on the soil -water-plant system in two different forest soils. This difference was attributed to (i) the soil characteristics, (ii) the application rates and (iii) whether or not nitrogen was applied. Long-term field experiments are required to test the performance and potential toxicity of these by-products as soil enhancers.